Efforts by Pregnant Women to Overcome Nausea and Vomiting Symptoms (Self-Management) for Emesis Gravidarum in the First Trimester - Lumastari Ajeng Wijayanti; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
Background : Emesis gravidarum is one of the most common complaints during the first trimester of pregnancy . Approximately 70–80% of pregnant women experience nausea and vomiting of varying severity . Appropriate self-management strategies are essential to reduce symptoms and prevent complications . Objective : To analyze pregnant women's self-management efforts in overcoming nausea and vomiting during the first trimester of pregnancy . Methods : This analytical descriptive study employed a cross-sectional design involving 100 first-trimester pregnant women experiencing emesis gravidarum . Respondents were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and the Chi- square test . Results : Most respondents demonstrated good self-management practices (68.0%). Common strategies included eating small frequent meals , avoiding fatty and strong-smelling foods , increasing rest , and consuming ginger . Maternal knowledge , family support , and health education were significantly associated with self-management practices (p<0.05). Conclusion : Maternal knowledge , family support , and health worker education significantly influence successful self-management of nausea and vomiting during early pregnancy . Keywords : emesis pregnancy , nausea and vomiting , pregnancy , self-management , first trimester